Resistin Impairs Insulin-Evoked Vasodilation - Gentile, Maria Teresa; Vecchione, Carmine; Marino, Gennaro; Aretini, Alessandra; Di Pardo, Alba; Antenucci, Giovanna; Maffei, Angelo; Cifelli, Giuseppe; Iorio, Luca; Landolfi, Alessandro; Frati, Giacomo; Lembo, Giuseppe (Diabetes (New York, N.Y.), 2008)
Resistin Impairs Insulin-Evoked Vasodilation Maria Teresa Gentile 1 , Carmine Vecchione 1 , Gennaro Marino 1 , Alessandra Aretini 1 , Alba Di Pardo 1 , Giovanna Antenucci 1 , Angelo Maffei 1 , Giuseppe Cifelli 1 , Luca Iorio 1 , Alessandro Landolfi 1 , Giacomo Frati 2 and Giuseppe Lembo 1 , 2 1 Department of Angio-Cardio-Neurology, Neuromed Institute, Pozzilli, Italy 2 Department of Experimental Medicine and Pathology, La Sapienza University of Rome, Rome, Italy Address correspondence and reprint requests to Giuseppe Lembo, MD, PhD, La Sapienza University of Rome, c/o Neuromed Institute, Località Camerelle, 86077 Pozzilli (IS), Italy. E-mail: lemboatneuromed.it Abstract OBJECTIVE —Since vascular dysfunction is a main trait of obese subjects, in the present study we evaluated the vascular impact of resistin, a recently discovered hormone markedly increased in obesity. RESEARCH DESIGN AND METHODS —We performed our analysis on aortic and mesenteric segments from young and old C57BL/6 mice and on cultured endothelial cells. Resistin-induced vascular effect was evaluated in vitro and in vivo. Molecular analyses were performed by immunoprecipitation and Western blotting. RESULTS —Recombinant murine resistin did not induce changes in either basal vascular tone or phenylephrine-induced vascular contraction. In contrast, both in vivo and in vitro administration of resistin significantly impaired dose-dependent insulin-evoked vasodilation by reducing endothelial nitric oxide synthase (eNOS) enzymatic activity. This effect of resistin was selective for insulin vascular action, since vasodilatation induced by increasing doses of acetylcholine or nitroglycerin was not influenced by the hormone. Molecular analysis of endothelial cells further detailed resistin-induced vascular resistance by showing impairment of insulin-evoked AKT and eNOS phosphorylations after exposure to resistin. Even this latter abnormality is selective of insulin signaling since AKT/eNOS phosphorylations are normally activated during acetylcholine stimulation. More important, the resistin-induced endothelial dysfunction depends on resistin's ability to alter insulin receptor substrate (IRS)-1 tyrosine/serine phosphorylation and its consequent interaction with phosphatidylinositol 3-kinase. CONCLUSIONS —Our results demonstrate that resistin is able to induce a selective vascular insulin resistance-impairing endothelial IRS-1 signaling pathway that leads to eNOS activation and vasodilation. eNOS, endothelial nitric oxide synthase IRS, insulin receptor substrate l -NAME, l - N G -nitro- l -arginine methyl ester PI, phosphatidylinositol Footnotes Published ahead of print at http://diabetes.diabetesjournals.org on 7 December 2007. DOI: 10.2337/db07-0557. The costs of publication of this article were defrayed in part by the payment of page charges. This article must therefore be hereby marked “advertisement” in accordance with 18 U.S.C. Section 1734 solely to indicate this fact. Received April 24, 2007. Accepted November 27, 2007. DIABETES